The Sputum Microbiome in Pulmonary Tuberculosis and Its Association With Disease Manifestations: A Cross-Sectional Study - Ticlla, Monica R.; Hella, Jerry; Hiza, Hellen; Sasamalo, Mohamed; Mhimbira, Francis; Rutaihwa, Liliana K.; Droz, Sara; Schaller, Sarah; Reither, Klaus; Hilty, Markus; Comas, Inaki; Beisel, Christian; et al. (Frontiers in Microbiology, 2021)
Each day, approximately 27 000 people become ill with tuberculosis (TB), and 4 000 die from this disease. Pulmonary TB is the main clinical form of TB, and affects the lungs with a considerably heterogeneous manifestation among patients. Immunomodulation by an interplay of host-, environment-, and pathogen-associated factors partially explains such heterogeneity. Microbial communities residing in the host's airways have immunomodulatory effects, but it is unclear if the inter-individual variability of these microbial communities is associated with the heterogeneity of pulmonary TB. Here, we investigated this possibility by characterizing the microbial composition in the sputum of 334 TB patients from Tanzania, and by assessing its association with three aspects of disease manifestations: sputum mycobacterial load, severe clinical findings, and chest x-ray (CXR) findings. Compositional data analysis of taxonomic profiles based on 16S-rRNA gene amplicon sequencing and on whole metagenome shotgun sequencing, and graph-based inference of microbial associations revealed that the airway microbiome of TB patients was shaped by inverse relationships between Streptococcus and two anaerobes: Selenomonas and Fusobacterium. Specifically, the strength of these microbial associations was negatively correlated with Faith's phylogenetic diversity (PD) and with the accumulation of transient genera. Furthermore, low body mass index (BMI) determined the association between abnormal CXRs and community diversity and composition. These associations were mediated by increased abundance of Selenomonas and Fusobacterium, relative to the abundance of Streptococcus, in underweight patients with lung parenchymal infiltrates and in comparison to those with normal CXRs. And last, the detection of herpesviruses and anelloviruses in sputum microbial assemblage was linked to co-infection with HIV. Given the anaerobic metabolism of Selenomonas and Fusobacterium, and the hypoxic environment of lung infiltrates, our results suggest that in underweight TB patients, lung tissue remodelling towards anaerobic conditions favours the growth of Selenomonas and Fusobacterium at the expense of Streptococcus. These new insights into the interplay among particular members of the airway microbiome, BMI, and lung parenchymal lesions in TB patients, add a new dimension to the long-known association between low BMI and pulmonary TB. Our results also drive attention to the airways virome in the context of HIV-TB coinfection.